INTRAVENOUS IRON THERAPY IN HEART FAILURE WITH REDUCED EJECTION FRACTION: EVIDENCE FROM RECENT TRIALS AND META-ANALYSES - Otasevic, Petar; Djordjic, Anastasia; Karadzic, Tatjana; Vuletic, Jelisaveta; Petrovic, Ivana (Medical Research, 2025)
Anemia is a frequently observed comorbidity in patients with heart failure (HF) and contributes to increased morbidity and mortality. Even though the etiology of anemia in HF patients is polymorphic, chronic inflammation and iron deficiency (ID) are reported as the most frequent underlying causes. Anemia is a strong prognostic marker in both acute and chronic HF, while ID, even in the absence of anemia, has a negative impact on patients’ symptoms, functional capacity, and quality of life (QOL). In chronic HF, functional ID is often present due to impaired iron utilization, but it may coexist with absolute ID, where iron stores are depleted. Intravenous (IV) iron therapy, has shown its beneficial effect in improving functional status, reducing symptoms, and lowering the rate of hospital readmissions. This has led to its inclusion in the latest guidelines of the European Society of Cardiology (ESC) as a recommended treatment for symptomatic patients with heart failure with reduced ejection fraction (HFrEF). Several studies have also described a consistent trend toward reduced mortality. The aim of this paper is to summarize current knowledge on the importance of ID and the therapeutic effects of iron supplementation in HFrEF patients. Timely recognition and correction of ID should be considered a cornerstone of individualized HfrEF management.